The unstoppable Wasp!. Unstoppable!. #3 - Whitley, Jeremy (Spotlight, 2020)
Ying, a girl raised with Nadia Pym, a.k.a. the Wasp, in a Russian lab, returns to bring her back but is stopped with the help of Moon Girl. Nadia then recruits two girls talented in the areas of physics and biology and genetics for her lab.